Konsep Jihad dalam Al-Quran - kerwanto kerwanto kerwanto (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
This article is a response to the growing radical understanding of religion and the rejection of Pancasila as the nation's ideology in the Unitary State of the Republic of Indonesia (NKRI). This article is also an offer of thought for the Deradicalization of Al-Quran Verses. Namely, as an effort to reinterpret several verses of the Qur'an which have the potential to be understood by some as the basis for acts of violence or coercion of certain ideologies. In this article, the author uses the theosophical esoteric interpretation approach such as Haidar Amuli (d. 1385), as an analytical tool to explore the content of several verses of the Qur’an related to jihad. This paper can also be referred to as thematic interpretation because the author tries to discuss (analyze) the content of the verses of the Qur'an based on a theme and tries to follow the steps of the thematic method in interpretation. Through an esoteric approach, in this article, jihad will not only be interpreted as a physical war taking up arms. Jihad has several levels of meaning, such as jihad of ahl shariah, ahl tariqah, and ahl haqiqa. Furthermore, by analyzing the historical context, the jihad verses can be interpreted as a movement for mental revolution and social moral improvement.